Involvement of phospholipids in the intoxication mechanism of botulinum neurotoxin - Kamata, Yoichi; Kimura, Yukiko; Kozaki, Shunji (Biochimica et biophysica acta, 1994)
Phospholipids were examined for their potential to interact with botulinum enurotoxin by an in vivo toxin-inactivation assay and a direct binding assay on a thin layer plate. Type E neurotoxin was inactivated by negatively charged phospholipids, phosphatidylserine (PS) and phosphatidylinositol (PI). The toxicity of the neurotoxin was not affected by phosphatidylcholine (PC) without an electric charge or phosphatidylethanolamine (PE) with a positive electric charge. The neurotoxin bound directly to PS and PI but not to PC or PE. These results suggest that the negatively charged phospholipids in the cell membranes are involved in the toxication mechanism of botulinum neurotoxin. The phospholipids PS and PI were tested for their potential to interact within three domains [L, H-1, and H-2] which compose the neurotoxin. All three domains bound to PS; whereas, PI specifically accepted the binding of the H-1 domain relative to the penetration of the neurotoxin into the lipid membrane. In this paper, we discuss the interaction between the neurotoxin and the lipid membrane in the intoxication mechanism.